2010
DOI: 10.1007/s00330-010-1990-5
|View full text |Cite
|
Sign up to set email alerts
|

Chest computed tomography using iterative reconstruction vs filtered back projection (Part 1): evaluation of image noise reduction in 32 patients

Abstract: Objective To assess noise reduction achievable with an iterative reconstruction algorithm. Methods 32 consecutive chest CT angiograms were reconstructed with regular filtered back projection (FBP) (Group 1) and an iterative reconstruction technique (IRIS) with 3 (Group 2a) and 5 (Group 2b) iterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
105
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(107 citation statements)
references
References 17 publications
2
105
0
Order By: Relevance
“…The CNR was almost doubled at the highest level of IR when compared to FBP in our measurements. Many studies have been published within the last years reporting on noise reduction and improvement of low-contrast image quality due to IR in CT examinations of the abdomen [13], the thorax [14,15] and the heart [25 -27]. In recent studies by Utsunomiya et al and Laqmani et al, a progressive improvement of the CNR and subjective image quality in cardiac CT and lowdose chest CT was reported when using different levels of IR compared to FBP [28,29].…”
mentioning
confidence: 99%
“…The CNR was almost doubled at the highest level of IR when compared to FBP in our measurements. Many studies have been published within the last years reporting on noise reduction and improvement of low-contrast image quality due to IR in CT examinations of the abdomen [13], the thorax [14,15] and the heart [25 -27]. In recent studies by Utsunomiya et al and Laqmani et al, a progressive improvement of the CNR and subjective image quality in cardiac CT and lowdose chest CT was reported when using different levels of IR compared to FBP [28,29].…”
mentioning
confidence: 99%
“…the deployment of bow-tie filters in cardiac imaging that aggressively restrict radiation beyond the targeted cardiac field-of-view [23], and recently the introduction of iterative reconstruction technique. Assessment of this technique by Potana et al [25,26] found significant image noise reduction without loss of diagnostic information on routine chest CT imaging in adults. On adopting a low-dose imaging technique (with 35% dose reduction), the iterative reconstructed image quality was found to be similar to a standard dose CT examination using filtered back projection reconstruction technique.…”
Section: Radiation Dosementioning
confidence: 99%
“…This includes a number of clinical studies. [18][19][20] Most assess image noise, contrast-to-noise ratio (CNR), signal-to-noise ratio (SNR), and radiologist ratings with paired analysis or Likert scale. However, it is well known that CNR is insufficient for quantifying medical image quality.…”
Section: Introductionmentioning
confidence: 99%